2003
DOI: 10.1183/09031936.03.00017903
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nasal and sinus nitric oxide output using single-breath humming exhalations

Abstract: Nasal nitric oxide (NO) levels increase greatly during humming compared to silent exhalation. In this study, the physiological and anatomical factors that regulate NO release during humming have been characterised in 10 healthy subjects and in a model of the sinus and the nose.Single-breath humming caused a large initial peak in nasal NO output, followed by a progressive decline. The NO peak decreased in a step-wise manner during repeated consecutive humming manoeuvres but recovered completely after a silent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 30 publications
7
79
0
2
Order By: Relevance
“…Though the study does not directly analyse the mechanism of NBE and its effects on AR, the author proposes a plausible explanation for the improvement in symptoms after NBE with the available literature on the subject. Various studies on nasal nitric oxide (nNO) in humans have revealed nitric oxide to be maximally produced from the nasal and paranasal sinus [11][12][13]. There have been also interesting analysis of humming and increased nNO as compared with normal quiet nasal exhalation suggesting improved paranasal sinus ventilation with this maneuver [14,15].…”
Section: Discussionmentioning
confidence: 96%
“…Though the study does not directly analyse the mechanism of NBE and its effects on AR, the author proposes a plausible explanation for the improvement in symptoms after NBE with the available literature on the subject. Various studies on nasal nitric oxide (nNO) in humans have revealed nitric oxide to be maximally produced from the nasal and paranasal sinus [11][12][13]. There have been also interesting analysis of humming and increased nNO as compared with normal quiet nasal exhalation suggesting improved paranasal sinus ventilation with this maneuver [14,15].…”
Section: Discussionmentioning
confidence: 96%
“…The oscillation generated by the humming is thought to increase gas exchange across the osteomeatal complex [90,92]. During tidal breathing, it can take up to 30 min to completely clear sinus gases into the nasal cavity, but with humming, this occurs in one exhalation [93,94]. In healthy volunteers, humming leads to a 15-fold peak in nasal nitric oxide, compared with quiet exhalation [90].…”
Section: Hypothesis 3: Nitric Oxide Is Trapped In the Obstructed Paramentioning
confidence: 99%
“…They include sex and sexual hormones, body weight and age, circadian changes of respiratory function in health and disease, caffeine and alcohol, meals rich in nitrate, genetic background for some enzymes, upper respiratory tract infection, exercise, drugs (including inhibitors of NO synthases) and of course smoking [46,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. Moreover, FeNO levels in healthy subjects are influenced by atopy, i.e.…”
Section: Exhaled Nitric Oxidementioning
confidence: 99%